Cognitive Function Tests: Application of MMSE and MoCA in Various Clinical Settings- a Brief Overview - Oleksy, Piotr; Zieliński, Karol; Buczkowski, Bartosz; Sikora, Dominik; Góralczyk, Ewa; Zając, Adam; Mąka, Magdalena; Papież, Łukasz; Kamiński, Jakub (Quality in Sport, 2024)
Introduction: Cognitive impairment can emerge as part of aging or from conditions affecting brain function, such as stroke, brain tumors, delirium, and neurodegenerative diseases. Effective cognitive assessment in clinical practice requires brief, reliable tests that evaluate specific cognitive domains. The MMSE (Mini-Mental State Examination) and MoCA (Montreal Cognitive Assessment) are among the most frequently used tools for these evaluations, each offering unique insights. Purpose of Research: This study aims to compare the effectiveness of MMSE and MoCA in diagnosing cognitive impairment and determining their suitability in various clinical settings and patient profiles. Materials and Methods: The analysis includes 61 articles from databases such as PubMed and Scopus, identified using keywords: Neuropsychological Tests, Cognitive Function Tests, MMSE and MoCA. Basic Results: The results indicate that MMSE, while effective for initial dementia screening, is less sensitive to mild cognitive impairment and influenced by education and age. MoCA offers higher sensitivity for MCI and early Alzheimer's stages, making it valuable as a complementary tool to MMSE. Conclusions: Combining MMSE and MoCA assessments can enhance diagnostic accuracy across diverse clinical contexts. Each tool’s unique strengths contribute to a more comprehensive cognitive assessment approach, optimizing diagnostic strategies for specific patient needs.